Reședința obișnuită a copilului părinții căruia locuiesc în state diferite [Articol] - Doni, Valentina (CEP USM, 2021)
The article discusses the main aspects of the habitual residence of the child with the parents that live in different states. After a short introductory part, there are analyzed the issues relating to the definition of habitual residence, the differences between habitual residence and other legal concepts, the importance of respecting the best interests of the child in the event of the detemination of habitual residence. It take into account the provisions of the Hague Convention on the Civil Aspects of International Child Abduction, the Civil Code of the Republic of Moldova, the Family Code of the Republic of Moldova, law no. 112 of 09.07.2020 for the amendment of certain normative acts. In the final part are presented the conclusions that emerge from this study.
THE HABITUAL RESIDENCE OF THE CHILD WHOSE PARENTS LIVE IN DIFFERENT STATES
Keywords: habitual residence; legal relation with a foreign element; connecting factors